Evaluation of bacterial presence on lead X-ray aprons utilised in the operating room via IBIS and standard culture methods. Issue 4 (July 2019) - Jain, Sameer; Rajfer, Rebecca A; Melton-Kreft, Rachel; Nistico, Laura; Miller, Mark C; Stoodley, Paul; Altman, Daniel T; Altman, Gregory T
Background: Despite precautions, surgical procedures carry risk of infection. Radiation-protective lead aprons worn by operating personnel are a potential source of bacterial contamination and have not been fully evaluated. Aim/objective: To evaluate lead aprons as a source of bacterial contamination, identify organisms most commonly found on this source, and devise a method with which to lower the risk of contamination. Methods: In this basic science study, 20 randomly selected lead X-ray aprons were swabbed at three time points. The experimental treatment was with a hospital-grade disinfectant wipe. The samples were assessed for bacterial growth via traditional plating methods and mass spectrometry. Plates were graded on a scale of 0 to 4+ based on the number of quadrants with growth. Growth on one quadrant or more was considered contaminated. Findings/results: Bacteria were initially detected via IBIS on a majority of the aprons (32/40), most commonly Staphylococcus epidermidis and Propionibacterium acnes . Virulent organisms cultured were Methicillin-resistant Staphylococcus epidermidis (MRSE), Neisseria, Streptococcus viridans and pseudomonas. MRSE were detected on 5/20 of the samples. Immediately after treatment, the majority of aprons showed less bacterial contamination (0/20 standard culture positive; 13/20 IBIS positive) with some recurrence at the 6-h time point (2/20 standard culture positive, 16/20 IBIS positive). All MRSE detected initially was eradicated. Discussion: Lead X-ray aprons worn in the operating room harbour bacteria. Disinfecting before use may prevent the introduction of virulent organisms to patients. Our proposed method of sanitising with a disinfectant wipe is quick and effective.